Relative contributions of bacteria and fungi to nitrous oxide emissions following nitrate application in soils representing different land uses. (April 2021) - Castellano-Hinojosa, Antonio; Le Cocq, Kate; Charteris, Alice F.; Abadie, Maider; Chadwick, David R.; Clark, Ian M.; González-López, Jesús; Bedmar, Eulogio J.; Cardenas, Laura M.
Abstract: Bacteria and fungi have been shown to produce nitrous oxide (N2 O) during denitrification, but their contribution after nitrate (NO3 − ) application to soil is not clearly established. In a microcosm experiment, the relative contribution of bacteria and fungi to N2 O and carbon dioxide (CO2 ) production by four contrasting soils representing different land uses after KNO3 addition was studied. The soils were daily wetted to 80% water-filled pore space (WFPS) and kept under greenhouse conditions for 10 days. The fungicide cycloheximide and the bactericide streptomycin were used to determine the possible microbial origin of the N2 O and CO2 emissions. Non-target effects of the antibiotics on the emission of N2 O and CO2 were evaluated using the inhibitor additivity ratio (IAR). The abundance of the bacterial and fungal communities was estimated by quantitative PCR (qPCR) of the bacterial 16S rRNA gene and the fungal internal transcribed spacer (ITS) region, respectively. The gene copy number of bacterial denitrifiers was calculated after quantification of the nirK, nirS, norB, nosZ I and nosZ II genes. After 10 d, regardless of the soil type, the cumulative N2 O emission from the soils treated with cycloheximide or streptomycin were similar. In all the four soils, N2 O fluxes were greater (on average 1.8 ± 0.3 times) in soils amended with the fungicide than with the bactericide during incubation for the first 48–96 h. Greater N2 O emissions (on average 1.7 ± 0.2 times) were detected in soils where bacteria were inhibited in comparison to those treated with the fungicide from 96 to 240 h. On average, 68.5% of the total CO2 emitted during the 10-d incubation period was produced in soils treated with the fungicide and 31.5% in those treated with the bactericide. The greater contribution of bacteria to the production of N2 O than fungi during the first 48–96 h was possibly due to a faster used of nitrate. Variations in the abundance of bacterial 16S rRNA genes, the ITS region, and the nirK, nirS, norB and nosZ I bacterial denitrification genes indicated that the antibiotics used to prevent the growth of bacteria and fungi were effective during incubation. These results suggest that both bacteria and fungi should be considered when designing and applying greenhouse gas mitigation strategies in soils and that their relative contribution to produce N2 O and CO2 can vary with time and nitrate availability. Highlights: In a 10-d microcosm experiment, bacteria dominated fungi for N2 O emissions during the first 3 d after N-fertilisation. Fungi dominated bacteria for N2 O emissions during the remaining 7-d of treatment. After 10-d, bacteria and fungi similarly contributed to N2 O production in the four soils analysed. Bacteria were greater CO2 producers than fungi after the 10-d treatment in the four soils analysed. Bacteria and fungi should be considered when designing greenhouse gas mitigation strategies.